Lessons to be learned from an attempted RCT: iCHIMPS—an online intervention for adolescents with mentally Ill parents - P. Dülsen; K. Barck; S. Wiegand-Grefe; A. Leidger; T. Paumen; H. Baumeister (Frontiers in Digital Health)
BackgroundChildren and adolescents with mentally ill parents represent an at-risk population for developing mental disorders themselves. Internet- and mobile-based interventions (IMIs) have been demonstrated to be an effective, scalable, and temporally and geographically independent method of treatment delivery. However, evidence for IMIs aimed at children and adolescents remains limited and inconclusive, especially for children of mentally ill parents. Therefore, the present trial aimed to evaluate the effectiveness of a mental health IMI (iCHIMPS) for children of parents with a mental illness. Due to insufficient recruitment, however, this article will primarily focus on lessons learned from the challenges encountered during the study’s implementation.MethodsThe IMI was targeted at children aged 12–18 years, regardless of whether they exhibited symptoms of mental disorders, provided that at least one parent had a diagnosed mental illness. To evaluate the effectiveness, the IMI was provided to one group [intervention group (IG)] while the control group received treatment as usual (TAU). At four measurement timepoints, the primary outcome (Youth Self-Report—YSR 11-18R) and various secondary outcomes were assessed. Recruitment from May 2021 to April 2023 initially took place at 21 participating mental health clinics throughout Germany and was later supplemented by various additional clinics as well as recruitment pathways.ResultsIn total, n = 22 participants were recruited. This result was far off the needed number of participants to meaningfully conduct any analyses. Therefore, no quantitative analyses were conducted, and this trial is discussed as a failed trial, providing important insights into ineffective strategies for reaching adolescents of parents with mental illnesses, in particular, and adolescents through digital interventions more generally.ConclusionThe identified reasons for the failed recruitment include the complex study design, particularly the presence of multiple concurrent trials recruiting from the same population, the inherent difficulty of reaching families with mentally ill parents, and the limitation of targeting the IMI solely at adolescents rather than involving families more broadly. Additionally, the design may not have been sufficiently engaging or appealing to adolescents. These reasons are discussed along with the implications for future IMI research involving children and adolescents. Clinical Trial Registrationidentifier (DRKS00025158).